The Slippery Slope Argument in the Context of Euthanasia and Assisted Suicide - A. V. Antipov (Концепт: философия, религия, культура, 2021)
This article analyzes the slippery slope argument and its application to the problem of legalizing euthanasia and physician-assisted suicide. The argument is often referred to in discussions of abortion, in vitro fertilization, etc., but it has been little developed in the Russian-language literature. This explains the relevance and novelty of this article. The focus is on the ways of representation of the argument in research. It distinguishes its main types: logical (disintegrating into no-principle distinction argument and the soritical argument), empirical (or psychological argument), and non-logical (metaphorical). Each of these types of argument is constructed according to a certain principle and has a number of features and critiques. A common place for criticism of an argument is its focus on the future so that it makes reasoning probabilistic. The logical type of argument is centered around denoting the transition between the original event and its adverse consequences and denotes the action of social factors to accelerate the transition. The no-principal distinction argument implies that there is no moral distinction between the events at the beginning and the end of the slope. The soritical argument involves intermediate steps between questionable and unacceptable practices. The conceptual slope is another variant of the logical kind of argument. The empirical argument illustrates a situation of changing societal values which results in an easier acceptance of morally disapproved practices. The metaphorical argument is used to illustrate the metaphor of slope and the situation of the accumulation of small problems that lead to serious undesirable results. The non-logical kind of argument centers around the routinization of practice, desensitization, and exploitation of unprotected groups in society. Exploitation can be called the victims' slope. It grounds its consideration on the abuse of the practice being administered. Application of the ethical methodology (theoretical-logical and empirical-historical) to the types of arguments and ways of their application allows us to highlight the value component of the argument, to determine its dilemma nature and to correlate it with bioethical principles. The application of bioethical principles to suppress the transition to undesirable consequences is critiqued on the basis of particularly difficult cases in which one is unable to articulate one's decision. The criticism of the argument is built on the probabilistic nature of the reasoning, the lack of reflection on the underlying premise and the lack of empirical evidence. It concludes that the slippery slope argument is incapable of being the only valid justification for rejecting the practices of physician-assisted suicide and euthanasia.